2018
DOI: 10.1002/lno.10772
|View full text |Cite
|
Sign up to set email alerts
|

Global patterns in phytoplankton biomass and community size structure in relation to macronutrients in the open ocean

Abstract: Owing to the dynamic nature of nutrient‐phytoplankton interactions, ambient macronutrient concentrations reveal little about the impact of nutrient availability on phytoplankton biomass and community composition at any given point in time or space. Here, however, we examine a global dataset (n = 262) where phytoplankton community structure and biomass are related to ambient concentrations of dissolved inorganic nitrogen (DIN), phosphate (P), and silicate. The macroecological patterns emerging from the analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 65 publications
4
17
2
1
Order By: Relevance
“…Ultimately, our results reinforce already existing ideas that nutrient availability can have an important bearing on the dominant cell size of phototrophs in nature [25,82,101104]. Clearly, the cyanobacteria S. salina could outcompete the eukaryotic alga T. suecia under severe nutrient limitation and all of the kinetic parameters we determined (Ks, V max , and β ), support this observation.…”
Section: Discussionsupporting
confidence: 88%
“…Ultimately, our results reinforce already existing ideas that nutrient availability can have an important bearing on the dominant cell size of phototrophs in nature [25,82,101104]. Clearly, the cyanobacteria S. salina could outcompete the eukaryotic alga T. suecia under severe nutrient limitation and all of the kinetic parameters we determined (Ks, V max , and β ), support this observation.…”
Section: Discussionsupporting
confidence: 88%
“…2c). The findings on the relationship between the nutrient condition and phytoplankton size structure have shown that small phytoplankton dominate under nutrient-poor conditions, and large phytoplankton dominate under relatively highnutrient conditions, regardless of the ocean type (open sea or coastal) [2,[5][6][7][8][9][10][11][12]. The result of this study, in which large phytoplankton dominated despite remarkably low nutrient concentrations, is contrary to the previous findings about the relationship between nutrient concentration and phytoplankton size structure.…”
Section: Discussioncontrasting
confidence: 86%
“…It is well known that the concentration of nutrients in an ecosystem significantly affects the size structure of the phytoplankton community. It has been reported from field surveys that large phytoplankton dominate under nutrient-rich conditions, whereas small phytoplankton dominate under oligotrophic conditions [2,[5][6][7][8][9][10][11][12]. The supply of nutrients to the upper layers is also important for controlling the size structure of the phytoplankton community [9,10,13].…”
Section: Introductionmentioning
confidence: 99%
“…Some critical issues concerning temporal lag in the physical‐biological coupling and the occurrence of transition states warrant further discussion. When using total phytoplankton biomass as a proxy for resource availability, we assume that resources have been incorporated into biomass (Duarte et al ; Gruner et al ; Mousing et al ). This process is relatively fast for individual phytoplankton cells.…”
Section: Discussionmentioning
confidence: 99%
“…To manage this issue, we used total phytoplankton biomass ( μ g C L −1 ) as a proxy for resource availability instead of in situ inorganic nutrients. Nutrient uptake and conversion into biomass occurred on very fast time scales for individual phytoplankton cells; thus, we assume that nutrient resources were incorporated into total phytoplankton biomass during our sampling and total phytoplankton biomass may serve as a reasonable proxy for resource supply (Duarte et al ; Gruner et al ; Mousing et al ). Total phytoplankton biomass was calculated from biovolume data using taxon‐specific equations for conversion (Table ).…”
Section: Methodsmentioning
confidence: 99%